(untitled) (Journal of Nuclear Technology in Applied Science, 2018)
The present study aims to improve the antioxidant and antimicrobialproperties of cake and produce low calorie cake through substitution of wheat flour (WF) by irradiated broccoli ( L.varpowder. In this study broccoli heads powder and broccoli leaves powder were gamma irradiated at dose levels of 0, 3, 5 and 7 kGy. Results showed that ethanolic (70%) extract of irradiated broccoli heads powder (IBHP) and irradiated broccoli leaves powder (IBLP) at a dose level of 5 kGy had higher total phenolic compounds (TPC) and antioxidant activity (AOA) compared to control and other doses. Thus, IBHP and IBLP at dose level of 5 kGy were selected for fortification of cake. IBHP was used to substitute (0, 1.5, 3, and 4.5 %) of WF in making cake, as well,replacement ofWF (0, 1, 2 and 3%) by IBLP. The results showed that the cake processed from IBHP and IBLP had pronounced improvement(%) in its chemical composition (protein, lipids, ash and fiber content) while, the energy value and carbohydrate content decreased with increasing the replacement level. Also, the results showed that the TPC content, AOA, volume and specific volume were increased by increasing substitution level of IBHP and IBLP compared to control samples. On the other hand,total intensity, L * and a* values of the crust and crumb were decreased, whereas Chroma and b* values were increased for crumb and decreased for crust for all cake treatments by the addition of IBHP and IBLP compared to control sample. For microbiological properties, the results